Interaction between the jogorku kenesh аnd the political regime in the implementation national security of Kyrgyzstan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the study of the theoretical aspects of national security and technologies of interaction between states and Parliaments. Analysis of political tasks and technologies of interaction between the state and the Jogorku Kenesh of the Kyrgyz Republic, which, through the prism of manipulative, normative, marketing, structural-functional, communicative and comparative approaches, made it possible to present models using the example of manipulation as a multidimensional socio-political phenomenon, as well as an integrated interdisciplinary system of knowledge.
Keywords: Jogorku Kenesh of the Kyrgyz Republic, national security of the Kyrgyz Republic, political management, public administration, national interests, national priorities, information analysis, interaction between the state and the Jogorku Kenesh, security threats, strategy for ensuring national security, concept of national security